1994
DOI: 10.1142/s0218339094000209
|View full text |Cite
|
Sign up to set email alerts
|

Lesioning McCloskey and Lindemann’s (1992) Mathnet: The Effect of Damage Location and Amount

Abstract: McCloskey and Lindemann [32] provide a simulation of brain damage on a neural network architecture and offer evidence that different lesions to a same network can lead to different error distributions. We briefly review the various kinds of networks that have been proposed to simulate various arithmetical fact retrieval phenomena and we present a simple network designed to make some computational constraints apparent. Additionally, we replicate McCloskey and Lindemann’s [32] simulation by training 5 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…the two arguments of the operation. In a later study, lesioned MATHNET models showed good adherence to neuropsychological data patients with brain damages [85]. However, the success of MATHNET in replicating human data can be entirely attributed to an implausible frequency manipulation [46].…”
Section: Simulation Of Number Cognition In Artificial Cognitive Systementioning
confidence: 99%
“…the two arguments of the operation. In a later study, lesioned MATHNET models showed good adherence to neuropsychological data patients with brain damages [85]. However, the success of MATHNET in replicating human data can be entirely attributed to an implausible frequency manipulation [46].…”
Section: Simulation Of Number Cognition In Artificial Cognitive Systementioning
confidence: 99%